Meta-Ureidophenoxy-1, 2, 3-triazole hybrid as a novel scaffold for promising HepG2 hepatocellular carcinoma inhibitors: Synthesis, biological evaluation and molecular docking studies. (15th November 2022) - Limpachayaporn, Panupun; Nuchpun, Sopon; Sirirak, Jitnapa; Charoensuksai, Purin; Wongprayoon, Pawaris; Chuaypen, Natthaya; Tangkijvanich, Pisit; Suksamrarn, Apichart
Graphical abstract: Highlights: Newly designed meta -ureidophenoxy-triazole scaffold was identified as a potential pharmacophore for efficient inhibition of HepG2. Majority of the compounds exhibited superior anti-HepG2 activity up to 4.9-fold to sorafenib. Selectivity index (SI) of 5r was enhanced to 5.2-time compared to the parental compound sorafenib. HepG2 treated with 5r resulted in similar percentage of apoptotic cells to treated with sorafenib. Abstract: Thirty-one meta -ureidophenoxymethyl-1, 2, 3-triazole derivatives were designed and synthesized via nucleophilic addition, nucleophilic substitution and copper-catalyzed azide-alkyne cycloaddition (CuAAC). The evaluation of their cytotoxicity using MTT assay indicated that almost all derivatives exhibited significantly superior inhibitory activity against hepatocellular carcinoma cell line HepG2 compared to the parental molecule sorafenib (1 ). Among the series, 5r was the most potent anti-HepG2 agent with IC50  = 1.04 µM, which was almost 5-fold more active than sorafenib (IC50  = 5.06 µM), while the cytotoxic activity against human embryonal lung fibroblast cell line MRC-5 remained comparable to sorafenib. The synthetic derivative 5r, thus, possessed 5.2-time higher selectivity index (SI) than that of sorafenib. Molecular docking studies revealed an efficient interaction of 5r at the same sorafenib's binding region in both B-Raf and VEGFR-2 with lower binding energies than those of sorafenib, consistent with its cytotoxic effect. Furthermore, 5r was proven to induce apoptosis in a dose-dependent manner similar to sorafenib. In addition, the prediction using SwissADME suggested that 5r possessed appropriate drug properties conforming to Veber's studies. These findings revealed that the newly designed meta -ureidophenoxy-1, 2, 3-triazole hybrid scaffold was a promising structural feature for an efficient inhibition of HepG2. Moreover, derivative 5r emerged as a promising candidate for further development as a targeted anti-cancer agent for hepatocellular carcinoma (HCC).